Baseline of distribution and origin of Rare Earth Elements in marine sediment of the coastal area of the Eastern Gulf of Tigullio (Ligurian Sea, North-West Italy). (June 2020) - Consani, Sirio; Cutroneo, Laura; Carbone, Cristina; Capello, Marco
Abstract: A study on the Rare Earth Element (REE) distribution in the bottom sediments of the Gulf of Tigullio (north-west Italy) was conducted. The results constitute a baseline for this zone of the Ligurian Sea and enabled the obtaining of valuable information on the origin and transport of sediments in the gulf. The distribution of REEs is controlled by phosphates, mainly monazite, and is generally homogeneous in the study area, reflecting the homogeneous distribution of the minerals. Some differences in REE and Sc distribution allow us to identify two sub-basins (Entella and Gromolo torrent sub-basins) characterised by slightly different geological frameworks. The "hat-shaped" observed patterns seem to indicate an overprinting of the original REE patterns due to exchanges between phosphates and seawater. REEs seem to be related with the rocks outcropping in the area, although an indirect effect of anthropic activity could be seen near a fish farm. Highlights: This paper gives the baseline values of REEs in the Eastern Gulf of Tigullio. REE distribution in this area is controlled by phosphates, particularly by monazite. REEs allowed to distinguish two different sub-basins. The observed "hat-shaped" REE patterns derive from phosphate-seawater exchanges. REEs have a natural origin, but a little anthropogenic effect could be observed.